2017
DOI: 10.1016/j.socscimed.2017.05.046
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear relationship between maternal work hours and child body weight: Evidence from the Western Australian Pregnancy Cohort (Raine) Study

Abstract: Using longitudinal data from the Western Australia Pregnancy Cohort (Raine) Study and both random-effects and fixed-effects models, this study examined the connection between maternal work hours and child overweight or obesity. Following children in two-parent families from early childhood to early adolescence, multivariate analyses revealed a non-linear and developmentally dynamic relationship. Among preschool children (ages 2 to 5), we found lower likelihood of child overweight and obesity when mothers worke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 34 publications
3
26
1
1
Order By: Relevance
“…Our study investigated the association during infancy, whereas prior US studies investigated the association among older-aged children. Several studies suggest that the association may differ by child age (12,13,17,22), and our findings generally supported this hypothesis. Our sample was lower income and had a lower level of educational attainment compared with prior studies and national averages.…”
Section: Original Articlesupporting
confidence: 89%
See 2 more Smart Citations
“…Our study investigated the association during infancy, whereas prior US studies investigated the association among older-aged children. Several studies suggest that the association may differ by child age (12,13,17,22), and our findings generally supported this hypothesis. Our sample was lower income and had a lower level of educational attainment compared with prior studies and national averages.…”
Section: Original Articlesupporting
confidence: 89%
“…These findings are generally consistent with US studies, which have reported that additional hours of maternal work increase the probability of childhood overweight/obesity (7,9,14). In an Australian sample, a larger magnitude of effect was observed among lower-income families (13) in contrast with results from Germany (12) and the United States (5,7-10), where larger effects were observed among higher-income families.…”
Section: Study Importancesupporting
confidence: 88%
See 1 more Smart Citation
“…Li and coauthors1 found that the effect of maternal long work hours on child overweight and obesity strengthened when fathers worked 45 hours or more per week in an Australian cohort. We examined three different definitions of fathers’ long work hours (≥45, ≥50 and ≥55), and there appeared an increasing trend in effects of maternal work hours as the threshold of fathers’ long work hours rose.…”
Section: Discussionmentioning
confidence: 99%
“…This co-occurrence has drawn much research attention to the link between the two trends 1. The vast majority of existing studies2–10 focused on US children.…”
Section: Introductionmentioning
confidence: 99%